Finite Element Model Based Determination of Local Membrane Conductivity of Polymer Electrolyte Fuel Cells. Issue 4 (1st April 2022) - Schuller, A.; Schmidt, T. J.; Eller, J.
Abstract : A new non-invasive method to determine PEFC in-plane membrane conductivity distribution is proposed. It is based on electrical impedance tomography that relies on surface current injection and voltage measurement at the outer cell surface. The working principle is detailed and a numerical feasibility study shows the potential of the technique. Different conductivity profiles could be reconstructed based on synthetic boundary voltage data with a high accuracy. A sensitivity analysis was performed to understand the influence of different types of noise and error sources. This new method has the potential to become a relevant tool for fuel cell diagnostic if the required accuracy can be reached in terms of electrode positioning, cell characterization and measurement system.